2021
DOI: 10.3390/molecules26092751
|View full text |Cite
|
Sign up to set email alerts
|

Tripodal, Squaramide-Based Ion Pair Receptor for Effective Extraction of Sulfate Salt

Abstract: Combining three features—the high affinity of squaramides toward anions, cooperation in ion pair binding and preorganization of the binding domains in the tripodal platform—led to the effective receptor 2. The lack of at least one of these key elements in the structures of reference receptors 3 and 4 caused a lower affinity towards ion pairs. Receptor 2 was found to form an intramolecular network in wet chloroform, which changed into inorganic–organic associates after contact with ions and allowed salts to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…These results suggest that the acetate is bound through hydrogen bonds with the N–H hydrogens of both ureas; this behavior has been widely described in the literature. , , Additionally, the signals of the naphthyl hydrogens adjacent to ureidic oxygen, which are influenced by hydrogen bonding, also shift downfield. The rest of the signals of the naphthyl hydrogens experienced an upfield shift because of a higher electron density due to the recognition of the anion by urea, possibly accompanied by an anion−π interaction. , It was observed that the phenyl protons of the receptors closest to the polyether chain experienced two behaviors in the cases of AcO – , BzO – , and H 2 SO 4 – titrations: first an upfield chemical shift change and then a downfield chemical shift change, thus indicating two equilibria in the complexation process. On the other hand, there were no significant changes for the methylene hydrogens of the polyether chain.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These results suggest that the acetate is bound through hydrogen bonds with the N–H hydrogens of both ureas; this behavior has been widely described in the literature. , , Additionally, the signals of the naphthyl hydrogens adjacent to ureidic oxygen, which are influenced by hydrogen bonding, also shift downfield. The rest of the signals of the naphthyl hydrogens experienced an upfield shift because of a higher electron density due to the recognition of the anion by urea, possibly accompanied by an anion−π interaction. , It was observed that the phenyl protons of the receptors closest to the polyether chain experienced two behaviors in the cases of AcO – , BzO – , and H 2 SO 4 – titrations: first an upfield chemical shift change and then a downfield chemical shift change, thus indicating two equilibria in the complexation process. On the other hand, there were no significant changes for the methylene hydrogens of the polyether chain.…”
Section: Resultsmentioning
confidence: 99%
“…The rest of the signals of the naphthyl hydrogens experienced an upfield shift because of a higher electron density due to the recognition of the anion by urea, possibly accompanied by an anion−π interaction. 33 , 34 It was observed that the phenyl protons of the receptors closest to the polyether chain experienced two behaviors in the cases of AcO – , BzO – , and H 2 SO 4 – titrations: first an upfield chemical shift change and then a downfield chemical shift change, thus indicating two equilibria in the complexation process. On the other hand, there were no significant changes for the methylene hydrogens of the polyether chain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This may reflect the intrinsic difficulties associated with the design and synthesis of receptors that extract salts from the aqueous layer to the organic phase, including selective extraction of extremely hydrophilic sulfate salts [35]. It has recently been found that a solution to this problem may lie in the use of ion pair receptors and certain squaramide derivatives have been shown to efficiently extract potassium sulfate from the aqueous to organic phase [36][37][38][39]. To the best of our knowledge, a combination of these two features, leading to molecules capable of selectively extracting sulfates and their fluorescent detection, has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%